Singular women : writing the artist - Frederickson, Kristen, 1965-; Webb, Sarah E. (University of California Press, 2003)
In this groundbreaking volume, contemporary art historians--all of them women--probe the dilemmas and complexities of writing about the woman artist, past and present. Singular Women proposes a new feminist investigation of the history of art by considering how a historian's theoretical approach affects the way in which research progresses and stories are told.